Pengaruh Booklet Terhadap Pengetahuan dan Sikap Kesehatan Reproduksi Calon Pengantin Terkait Pencegahan Risiko Kehamilan di Kabupaten Pemalang - Heni Irawati; Apoina Kartini; Sri Achadi Nugraheni (Jurnal Manajemen Kesehatan Indonesia, 2019)
One of the causes of a high maternal mortality rate is the low knowledge of women's reproductive health, especially about the prevention of pregnancy risks. This can be overcome by increasing the knowledge of prospective brides, one of them is by providing health education with booklet media. The purpose of this study was to determine the effect of booklets on the knowledge and attitudes of reproductive health of brides related to the prevention of the pregnancy risks.       This type of research is quasi-experimental with a non-equivalent control group design. The study population was the future brides who attended the course of Future Bride and Groom at the Religious Affairs Office in Pemalang Regency. The samples were 50 brides for the intervention group and 50 brides for the control group. The instruments were questionnaires and booklets. An intervention group and a control group were compared based on the result of pre and post intervention. Statistical analysis used t-test and mann whitney test.       The results showed that there is a differentiation in reproductive health knowledge after intervention between intervention group and control group (p = 0,000 <0,05) and there is a differentiation in reproductive health attitudes after intervention between intervention group and control group (p = 0,008 <0,05). The knowledge average of future brides increased by 4.28 points and the attitude average increased by 1.84 points after intervention.       It can be concluded that the booklet can be used to increase the reproductive health knowledge and attitudes of future brides in prevention of pregnancy risks, especially in the case of anemia causing bleeding, chronic energy deficiency, and puerperal danger signs. It is recommended that the booklet can be developed as a media for reproductive health education in the course of Bride and Groom at the Religious Affairs Office.Key Words: Reproductive health; Knowledge; Attitudes; Booklet; Brides